(untitled) (Journal of Economic Research & Business Administration, 2016)
For planning the tax burden it is important to keep track of changes in tax legislation in order to use various tax incentives and other means provided for by the legislation reducing the tax burden. The aim is primarily balancing the interests of the state and taxpayers. That is, the taxpayer has the right to use the optimization techniques provided by the legislation of tax payments and thus reduce the tax burden. In this case we are talking about the optimization tax planning. Tax planning optimization based on the use of tax optimization schemes, that is, ways of registration and representation of economic activities that allow the taxpayer to apply a favorable tax regime and savings on taxes. This type of tax planning is the most common in the world practice. According to various estimates, from 50 to 80% of domestic enterprises have resorted to the different methods of optimizing the planning and determination of the tax burden.